One Throne, One Identity: Pronominal and Syntactical Analysis of ??? Epexegetis in New Testament Monotheism - Matthews, Yoce Daniel (International Journal Labs, 2026)
Debates on New Testament monotheism often center on the function of the conjunction kai (???) within sequences of divine titles, particularly whether it separates two persons or reinforces a single identity. Objective: This study examines whether kai can function epexegetically (“that is” / “even”) to affirm the unity of God’s personal identity, focusing on Mark 12:29 and Revelation 22:3–4. Employing a qualitative approach, this research utilizes content analysis and grammatical-historical exegesis of the NA28 Greek text, integrating syntactical analysis, application of Granville Sharp’s rule in article–noun–kai–noun constructions, and discourse grammar to assess how grammatical choices shape identity claims. In Mark 12:29, the citation of the Shema presents a concentration of the titles Kyrios and Theos to emphasize a single divine subject, establishing a theological framework for subsequent Christological texts. Further analysis suggests that in several constructions (Eph 5:5; 2 Tim 4:1; 1 Tim 2:5), kai functions not merely as a distributive conjunction but as a marker of unified identity, linking distinct titles or roles to the same referent. Crucially, Revelation 22:3–4 employs singular pronouns (?????/????) following the phrase “God and the Lamb,” which linguistically supports an epexegetical reading. The New Testament writers uphold monotheism consistent with divine immutability, presenting Jesus Christ as fully participating in the identity of the one God, with epexegetical kai serving as a key syntactical mechanism in affirming that unity.